The Past, Present, and Future of African American Literary History (KULT_online, 2012)
At a time when the project of literary history is eyed with increasing suspicion, two recent publications expand and complicate discussions of what constitutes the canon of African American literature: With their Cambridge History of African American Literature, Maryemma Graham and Jerry Ward have edited an impressive, comprehensive survey that will no doubt impact further discussions on the development of African American literature in the early 21st century. While its chapters offer a multiperspective view that defies any single narrative to explain 'AfAm Lit', Kenneth Warren, by asking the polemical question of What Was African American Literature?, tells quite a revisionary story: African American literature, Warren claims, was first and foremost a "representational and rhetorical strategy" (p. 9) in response to the social reality of the Jim Crow era, and therefore no longer exists. Particularly in conjunction with each other, these two publications might represent a crucial moment in African American literary studies, as many of the well-established theoretical and ideological frameworks are being renegotiated.